2011
DOI: 10.1186/1471-2407-11-18
|View full text |Cite
|
Sign up to set email alerts
|

A novel insight of sentinel lymph node concept based on 1-3 positive nodes in patients with pT1-2 gastric cancer

Abstract: BackgroundSentinel node (SN) biopsy has been practiced in gastric cancer in recent years, and many studies focused on the distribution of solitary lymph node metastasis (SLM) to assess the pattern of SN. In fact, there is usually more than one SN existing in gastric cancer. The distribution of SNs needs to be further re-evaluated.MethodsA total of 289 patients in pT1-2 stage with 1-3 positive nodes confined to same compartment were included in this study with informed consents. The primary lesion was solitary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 24 publications
4
19
0
Order By: Relevance
“…This unusual pattern of LN metastasis has been reported in various cancers, such as breast, colon, and lung cancer [3][4][5]. Several studies have also reported on skip metastasis in gastric cancer [7][8][9], in which the following factors could play a role: (1) occult metastasis or micrometastasis which was missed during routine examination of the perigastric (PG) area [10]; (2) direct lymphatic flow from the tumor to LNs in the extraperigastric (EP) area, bypassing the PG area [11-13; and (3) free cancer cells passing through PG LNs because of an unfit microenvironment for settling [14]. Despite previous reports, the prognosis and mechanism of skip metastasis in gastric cancer are not congruent because the number of cases in each study was limited.…”
Section: Introductionmentioning
confidence: 65%
“…This unusual pattern of LN metastasis has been reported in various cancers, such as breast, colon, and lung cancer [3][4][5]. Several studies have also reported on skip metastasis in gastric cancer [7][8][9], in which the following factors could play a role: (1) occult metastasis or micrometastasis which was missed during routine examination of the perigastric (PG) area [10]; (2) direct lymphatic flow from the tumor to LNs in the extraperigastric (EP) area, bypassing the PG area [11-13; and (3) free cancer cells passing through PG LNs because of an unfit microenvironment for settling [14]. Despite previous reports, the prognosis and mechanism of skip metastasis in gastric cancer are not congruent because the number of cases in each study was limited.…”
Section: Introductionmentioning
confidence: 65%
“…It is well known that lymph node metastasis (LM) is an important prognostic risk factor. [ 6 , 7 , 8 ] And individualized treatment for GC patients requires selection reasonable therapeutic schedule according to patient’s specific situation ; one important aspect is the evaluation for LM. LM in gastric cancer is nevertheless significantly complicated, with many related factors [ 9 , 10 ], and there is still no good method to predict it.…”
Section: Introductionmentioning
confidence: 99%
“…SM usually occur along the left gastric artery, anterior common hepatic artery but can also be cited along coeliac or splenic artery. Huang et al ( 22 ) reported that transverse lymphnode metastasis were found in as high as 50% of patients with tumor located on the greater curvature, but the inclusion criteria on this study, as well as the surgery performed, have some blurred spots. There are many theories regarding the explanation of this phenomenon, based on the lymphatic drain of the stomach ( 23 , 24 ), the possible “hostile” microenvironment of level 1 nodes ( 24 ), obstruction of the main lymphatic rout by cancer, low concentration of certain adhesion molecules, etc.…”
Section: Incidence Of Solitary Lymphnode Metastasis (Slm)mentioning
confidence: 66%